Effect of nephroprotectors of javanese bark extract (Lannea coromandelica) on aspirin-induced rat serum creatinine levels - Jastria Pusmarani; Mus Ifaya; Risky Juliansyah Putri; Ade Safitri (Journal of Health Management and Pharmacy Exploration, 2023)
Kidney disease is a global health problem based on the increase of incidence, prevalence, and morbidity rate. According to RISKESDAS 2018, the prevalence of chronic kidney disease (CKD) was increased significantly. Lannea coromandelica stem bark contains flavonoid was exhibited antioxidant that could be potential as nephroprotector. This study aimed to find out the nephroprotector effect of ethanolic extract of Lannea coromandelica stem bark by measurement serum creatinine levels at rats (Rattus novergicus). This study was used experimental laboratory method. In this study used 25 rats were divided into 5 groups. Group 1 was administered Na CMC 1 % as negative control group. Group 2 was administered aspirin 600 mg/kg body weight as induced control group. Group 3, 4, and 5 were administered Lannea coromandelica stem bark ethanolic extract with the doses 400 mg/kg body weight, 800 mg/kg body weight, and 1200 mg/kg body weight, respectively. The extract of lannea coromandelica stem bark groups were given for 4 days orally. Blood of rats were collected from the orbital sinus eye to be measured creatinine serum level at 5th day. The data was analyzed statistically with one way ANOVA and Paired samples test. The result of this study exhibited that there was a differences of creatinine levels between pre and post treatment with p-value=0.033< 0.05. In conclusion, this study presented that ethanolic extract of Lannea coromandelica stem bark was decreased serum creatinine levels at doses 800 and 1200 mg/kg body weight against the aspirin induced on rats.